2019
DOI: 10.1111/aor.13581
|View full text |Cite
|
Sign up to set email alerts
|

Efficient decellularization of equine tendon with preserved biomechanical properties and cytocompatibility for human tendon surgery indications

Abstract: Chronic and acute tendon injuries are frequent afflictions, for which treatment is often long and unsatisfactory. When facing extended injuries, matrices and scaffolds with sufficient biomechanical properties are required for surgical repair and could additionally serve as supports for cellular therapies to improve healing. In this study, protocols of either commonly used detergents only (SDS 1%, Triton 1%, TBP 1%, and Tween‐20 1%) or a combination of freeze/thaw (F/T) cycles with decellularization agents (NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 47 publications
3
55
0
Order By: Relevance
“…Applications : Alcohol is commonly used in disinfection of skin and precision instruments, etc. There are many reports on the use of alcohol to disinfect dECM, which are mainly derived from pericardium [ 11 ], valve [ 123 , 124 ], blood vessel [ 12 , 121 , 125 , 126 ], liver [ [127] , [128] , [129] ], pancreas [ 130 ], trachea [ 131 ], bladder [ 130 , [132] , [133] , [134] , [135] ], kidney [ 48 , 136 ], bone [ 137 , 138 ], tendon [ [139] , [140] , [141] ] and nerve [ 142 ].…”
Section: Sterilization and Disinfection Methods Of Decmmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications : Alcohol is commonly used in disinfection of skin and precision instruments, etc. There are many reports on the use of alcohol to disinfect dECM, which are mainly derived from pericardium [ 11 ], valve [ 123 , 124 ], blood vessel [ 12 , 121 , 125 , 126 ], liver [ [127] , [128] , [129] ], pancreas [ 130 ], trachea [ 131 ], bladder [ 130 , [132] , [133] , [134] , [135] ], kidney [ 48 , 136 ], bone [ 137 , 138 ], tendon [ [139] , [140] , [141] ] and nerve [ 142 ].…”
Section: Sterilization and Disinfection Methods Of Decmmentioning
confidence: 99%
“…Tendons mainly come from bovine, horse and pig, and a small number of tendons are from human, rabbit, sheep, dog. The sterilization and disinfection methods of decellularized tendon mainly include ethanol [ [139] , [140] , [141] ], EO [ [78] , [79] , [80] ], PAA [ 95 , 96 ], irradiation [ 27 , [54] , [55] , [56] ], antibiotics [ 153 , 179 ] and ScCO 2 [ 55 ], etc.…”
Section: Sterilization and Disinfection Methods Of Various Common Decmentioning
confidence: 99%
“…The efficacy of tendon transfer is hindered by accelerated graft degeneration and would largely benefit from therapeutic cell stimulation, ideally leading to optimal elasticity, mobility, and tensile strength restoration (O'Brien, 1997;Kannus, 2000). Bioengineering scaffolds of interest, such as human cadaveric and equine decellularized tendons or artificial equivalents, enable optimal maintenance of biocompatibility, mechanical properties, and susceptibility for cell seeding, whereas autologous vestigial tendons remain as the standard of care (Wehbé, 1992;Chong et al, 2009;Jakubietz et al, 2011;Pridgen et al, 2011;Burk et al, 2016;Lovati et al, 2016;Valentin et al, 2016;Aeberhard et al, 2019). Vast arrays of potential therapeutic cell types have been investigated in tendon bioengineering for regeneration enhancement, including tendon sheath fibroblasts, adult tenocytes, stem cells, placenta cells, amniotic cells, and platelet-derivatives (Kadner et al, 2002;Kaviani et al, 2002Kaviani et al, , 2003Awad et al, 2003;Chen et al, 2009;Akhundov et al, 2012;Xu et al, 2013;Petrou et al, 2014).…”
Section: Phenotypic Stability Chondrogenic Potential and Biomechanicsmentioning
confidence: 99%
“…One approach to eliminating the risk of disease transmission or immune reactions and improving the availability of scaffolds is the decellularization process, which transforms a scaffold into a shelf product [ 14 16 ]. Decellularized tendon scaffolds (DTSs) are prepared from different protocols that include a combination of physical, chemical and enzymatic techniques [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decellularized tendon scaffolds (DTSs) are prepared from different protocols that include a combination of physical, chemical and enzymatic techniques [ 17 , 18 ]. Recent studies have shown reproducible results in biomechanical and histological evaluations for protocols that include combinations of chemical and enzymatic decellularization agents [ 16 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%